1994
DOI: 10.1103/physrevlett.72.2769
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Wannier-Stark transitions and miniband Franz-Keldysh oscillations in strongly coupled GaAs-AlAs superlattices

Abstract: Using differential photocurrent spectroscopy we have studied the field dependent absorption in a GaAs/AlAs superlattices, which have only one monolayer AlAs barriers, with unpreceded dynamical resolution. We are able to resolve a symmetric Wannier-Stark (WS) fan up to an index of plus/minus 9 and for the first time Franz-Keldysh (FK) oscillations across the whole energy width of the lowest combined miniband. A modulation of the WS transitions by FK oscillations (and vice versa) is clearly visible. We also pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…More recent studies refer to the transition between the Franz-Keldysh oscillations and the WannierStark ladder [26], and the influence of higher valleys in the band structure [27].…”
Section: Experimental Summarymentioning
confidence: 99%
“…More recent studies refer to the transition between the Franz-Keldysh oscillations and the WannierStark ladder [26], and the influence of higher valleys in the band structure [27].…”
Section: Experimental Summarymentioning
confidence: 99%
“…In Fig. 2, fine oscillation structures appear in the electric-fieldstrength region below 20 kV/cm, which results from FranzKeldysh (FK) oscillations related to the miniband structures [13]. With an increase in electric field strength, the FK oscillation disappears, which originates from the localization of the envelope functions, then the ER signal related to the interband transition, which is labeled H11(0), between the E1(0) state and the n = 1 heavy-hole [HH(0)] state appears at ~1.568 eV.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, Schmidt et al [9] and Linder et al [10] reported the FK oscillations at the miniband edge in a GaAs/AlAs SL with a very wide miniband (∼330 meV for the first electron miniband) by using differential photocurrent (PC) spectroscopy. They suggested the coexistence of the FK oscillations and the WS localization.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we have investigated the FK oscillations at the miniband edge in a GaAs/Al 0.1 Ga 0.9 As SL embedded in a p-i-n structure by using electroreflectance (ER) spectroscopy which is a major method used to observe the FK oscillations in bulk semiconductors. The width of the first electron miniband is estimated to be 27 meV which is much narrower than that of the sample used in [9,10]. The profiles of the FK oscillations remarkably depend on the electric field: the oscillation direction changes from the low-energy side to the high-energy side with the increase of the electric field, then the FK oscillations disappear in the high-field regime of the WS localization.…”
Section: Introductionmentioning
confidence: 99%